2014
DOI: 10.4028/www.scientific.net/msf.804.209
|View full text |Cite
|
Sign up to set email alerts
|

The Photocatalytic Degradation of Methomyl over TiO<sub>2</sub> Nanopowder Prepared by the Low Temperature Solvothermal Route

Abstract: Titanium dioxide (TiO2) nanopowder was prepared by the low temperature solvothermal route with starting chemicals containing titanium isopropoxide, ammonium hydroxide, nitric acid and ethanol in a PTFE–lined autoclave. The final pH of the mixed solution was 1 and treated at 100 °C for 2–6 h. The white precipitated was filtered and dried in an oven at 80 °C for 24 h. The phase transition was characterized by X–ray diffractometer (XRD). Single phase anatase structure was obtained without calcination step. The mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 12 publications
(11 reference statements)
0
1
0
Order By: Relevance
“…XRD pattern of TiO 2 powder synthesized via the solvothermal method at 100°C for 5h as shown in [11], which corresponded to the previously reported [12]. The crystal size of anatase TiO 2 was calculated from the X-ray diffraction peak according to the Scherrer's equation [13]:…”
Section: Resultssupporting
confidence: 72%
See 1 more Smart Citation
“…XRD pattern of TiO 2 powder synthesized via the solvothermal method at 100°C for 5h as shown in [11], which corresponded to the previously reported [12]. The crystal size of anatase TiO 2 was calculated from the X-ray diffraction peak according to the Scherrer's equation [13]:…”
Section: Resultssupporting
confidence: 72%
“…These results are reasonably explained by in term of light-shielding effect, while excessive amounts of TiO 2 powder in solutions would decrease the light penetration [8]. The photocatalytic degradation efficiency was better than the previously reported [12]. For the degradation mechanism has reported that the bonds of methomyl are cleaved to produced the intermediates C 2 H 4 NO and C 3 H 6 NS as well as a small amount of NO 2 are formed.…”
Section: Resultsmentioning
confidence: 75%
“…TiO 2 powder was synthesized via the single step solvothermal method without calcination. The synthesis of TiO 2 was carried out following the method reported elsewhere [9]. Titanium isopropoxide (97%, Aldrich, England), ammonium hydroxide (NH 4 OH, 29.4%, J.T.Baker, U.S.A.), nitric acid (65%, Merck, Germany) were used as the starting materials and ethanol (99.9%, Merck, Germany) was used as solvent.…”
Section: Methodsmentioning
confidence: 99%
“…It is well known that pesticide degradation is a process whereby activation energy is released. The increase in temperature destroys the former steady-state equilibrium, resulting in the degradation equilibrium shifting to the elimination reaction in which a lot of energy is absorbed (Tao & Tang 2004, Pookmanee et al 2014. As a result, the amount of methomyl decreased with increasing temperature.…”
Section: Temperaturementioning
confidence: 99%